Partisipasi Organisasi Karang Taruna Di Dalam Lingkungan Masyarakat Desa Jati Sidoarjo - Rachmawati Fidia Cahyani Sugistin; Wahyu Eko Pujianto (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
The Karang Taruna Organization (KARTAR) in Jati Sidoarjo Village, especially KARTAR RW 01, has become a significant entity in community development and empowerment efforts. With various work programs and activities, KARTAR RW 01 has succeeded in making positive contributions that have had an impact on revitalizing the spirit of youth participation. Through purchasing glass drinks when someone dies, environmental activities, and security monitoring by providing CCTV, KARTAR RW 01 is able to create a better community environment. The impact of this participation can be seen in easing the economic burden on the community, increasing environmental security, and reviving the spirit of participation of young people who were previously less involved in community activities. Regulatory support, such as Youth Law no. 40 of 2009 and Minister of Home Affairs Regulation Number 114 of 2014, strengthen the role of KARTAR RW 01 in youth empowerment. As an awareness agent, this organization not only participates in physical activities but is also involved in increasing the awareness and sensitivity of the younger generation towards the surrounding environment. The concept of youth participation in development, in line with national ideals and regulations governing youth empowerment, is reflected in the practices of KARTAR RW 01. This organization is not only an implementer, but also a pioneer of these values ​​in every activity. Thus, youth participation in KARTAR RW 01 is not only fulfilling social responsibility, but also becoming a real means of achieving national goals in developing an inclusive, just and sustainable society.